2021
DOI: 10.3389/fimmu.2021.787797
|View full text |Cite
|
Sign up to set email alerts
|

The Prebiotic Effects of Oats on Blood Lipids, Gut Microbiota, and Short-Chain Fatty Acids in Mildly Hypercholesterolemic Subjects Compared With Rice: A Randomized, Controlled Trial

Abstract: Phytochemicals derived from oats are reported to possess a beneficial effect on modulating dyslipidemia, specifically on lowering total and LDL cholesterol. However, deeper insights into its mechanism remain unclear. In this randomized controlled study, we assigned 210 mildly hypercholesterolemic subjects from three study centers across China (Beijing, Nanjing, and Shanghai) to consume 80 g of oats or rice daily for 45 days. Plasma lipid profiles, short chain fatty acids (SCFAs), and fecal microbiota were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 68 publications
2
21
0
1
Order By: Relevance
“…The effect of oat and barley β-glucan on HDL cholesterol is not conclusive as the results show trends for a reduction that are only significant for the intervention with barley flakes ( Tables 6 , 7 ). This is also in line with the meta-analysis of Whitehead et al ( 57 ) and study of Xu ( 42 , 60 ) who showed no effect on HDL cholesterol or a significant heterogeneity among studies ( 57 ).…”
Section: Discussionsupporting
confidence: 87%
“…The effect of oat and barley β-glucan on HDL cholesterol is not conclusive as the results show trends for a reduction that are only significant for the intervention with barley flakes ( Tables 6 , 7 ). This is also in line with the meta-analysis of Whitehead et al ( 57 ) and study of Xu ( 42 , 60 ) who showed no effect on HDL cholesterol or a significant heterogeneity among studies ( 57 ).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, one mechanistic study indicated that the increased processes of glucose oxidation and insulin clearance, as well as the decreased process of fatty acid release, were the two key actions of SCFA in improvements of insulin sensitivity ( 87 ). Consistent with clinical controlled trials, the beneficial effects of dietary fiber intervention on plasma insulin and circulating SCFA have also been observed by researchers ( 88 , 89 ). However, it should be noted that β-glucan failed to confer a beneficial effect on the improvement of FPI when we performed a subgroup analysis by the type of intervention; the results were consistent with several published meta-analyses ( 51 , 90 ) but contradictory to the meta-analysis conducted by Bao et al ( 91 ).…”
Section: Discussionsupporting
confidence: 78%
“…According to the research by Christine et al ( 40 ), an increase in the intake of dietary fiber by 5 g per day can decrease the risk of disease progression or mortality by 30% and facilitate immune therapy. Besides, according to the research by Xu et al ( 41 ), oats can reduce total cholesterol content and low-density lipoprotein content and possess the benefits of a prebiotic.…”
Section: Results and Analysismentioning
confidence: 99%